TINJAUAN TERHADAP TEORI POSITIVISME HUKUM DALAM SISTEM PERADILAN PIDANA INDONESIA - Faissal Malik (Jurnal Pendidikan Kewarganegaraan Undiksha, 2021)
This study aims to (1) identify and analyze how positivism theory represents the value of justice and legal certainty, and (2) know and analyze how legal theory prevails in Indonesia. This type of research is normative legal research. The data obtained from this research is secondary data obtained through library research, then the data obtained is analyzed juridically qualitatively through a statutory and conceptual approach. The results of this study indicate that (1) In legal positivism, the entire statutory regulation is essentially something that contains the law completely so that the next task of the judge is to apply the provisions of the law mechanically in solving problems in society, in accordance with (2) The conception of the theory of development law is adequate law and does not view law as a set of rules and principles governing human life, but also includes institutional institutions and processes needed to realize the law. become reality. Meanwhile, the Pancasila Legal Theory is a legal theory which is based on the values of Pancasila as the ontological, epistemological and axiological basis based on the principles of Pancasila law.